Persebaran Islam dan Kontribusinya terhadap Masyarakat Afrika Sub-Selatan Sahara - Karmanah, Ade (Buletin Al-Turas, 2004)
The spread of islam in African region began since the fast period of Risalah. Islamic Civilization colered theÂ way of life of the society, like clothes values, and arts. This civilization also improved their live ideologically,economical, socially, politically, and culturally.Â